PFKFB3 Regulates Chemoresistance, Metastasis and Stemness via IAP Proteins and the NF-κB Signaling Pathway in Ovarian Cancer - Jiang, Yu-xin; Siu, Michelle K. Y.; Wang, Jing-jing; Leung, Thomas H. Y.; Chan, David W.; Cheung, Annie N. Y.; Ngan, Hextan Y. S.; Chan, Karen K. L. (Frontiers in Oncology, 2022)
Glycolysis has been reported to be critical for cancer stem cells (CSCs), which are associated with tumor chemoresistance, metastasis and recurrence. Thus, selectively targeting glycolytic enzymes may be a potential therapy for ovarian cancer. 6‐phosphofructo‐2‐kinase/fructose‐2,6‐biphosphatase 3 (PFKFB3), the main source of fructose-2,6-bisphosphate, controls the first committed step in glycolysis. We investigate the clinical significance and roles of PFKFB3 in ovarian cancer using in vitro and in vivo experiments. We demonstrate that PFKFB3 is widely overexpressed in ovarian cancer and correlates with advanced stage/grade and poor outcomes. Significant up-regulation of PFKFB3 was found in ascites and metastatic foci, as well as CSC-enriched tumorspheres and ALDH+CD44+ cells. 3PO, a PFKFB3 inhibitor, reduced lactate level and sensitized A2780CP cells to cisplatin treatment, along with the modulation of inhibitors of apoptosis proteins (c-IAP1, c-IAP2 and survivin) and an immune modulator CD70. Blockade of PFKFB3 by siRNA approach in the CSC-enriched subset led to decreases in glycolysis and CSC properties, and activation of the NF-κB cascade. PFK158, another potent inhibitor of PFKFB3, impaired the stemness of ALDH+CD44+ cells in vitro and in vivo, whereas ectopic expression of PFKFB3 had the opposite results. Overall, PFKFB3 was found to mediate metabolic reprogramming, chemoresistance, metastasis and stemness in ovarian cancer, possibly via the modulation of inhibitors of apoptosis proteins and the NF-κB signaling pathway; thus, suggesting that PFKFB3 may be a potential therapeutic target for ovarian cancer.